Code Mixing as Fashion Discourse: The Use of English Fashion Registers in Aquinaldo Adrian’s Tiktok Content - Naufaldi Athallah; Andang Saehu; Hasbi Assiddiqi (Universitas Pahlawan Tuanku Tambusai, 2026)
The increasing use of English in Indonesian digital media has contributed to the widespread practice of code mixing, particularly in fashion-related content on TikTok. One notable form of this phenomenon is the use of **English fashion registers**, which refer to specialized English vocabulary and expressions commonly used to describe fashion products, styling techniques, garment features, and trends within the fashion industry. This study aims to identify the types and reasons for code mixing involving English fashion registers in Aquinaldo Adrian’s TikTok review and styling videos. A descriptive qualitative method with a sociolinguistic approach was employed. Data were collected from twenty-four review and styling videos uploaded between March and May 2026 and analyzed using Hoffmann’s (1991) theory of code mixing. The findings identified 838 instances of code mixing, comprising intra-sentential code mixing (595 occurrences; 71%) and intra-lexical code mixing (243 occurrences; 29%). Two primary reasons for code mixing were identified: talking about a particular topic and expressing group identity. The findings demonstrate that English fashion registers function not only as specialized terminology but also as linguistic resources through which Indonesian fashion content creators communicate domain-specific concepts and construct professional and social identities within contemporary digital fashion discourse.